Feeding/Eating problems in children: Who does (not) benefit after behavior therapy? A retrospective chart review - Dumont, Eric; Jansen, Anita; Duker, Pieter C.; Seys, Daniel M.; Broers, Nick J.; Mulkens, Sandra (Frontiers in Pediatrics, 2023)
Abstract Background: Treating disordered feeding at a young age reduces risks of future feeding problems, but not all children profit equally; can we define predictors of a worse prognosis? Objectives: In 252 children, with a mean age of 4;7 years (SD=3 years; range 5 months to 17;10 years), who had undergone behavioral day treatment in the past, several variables were investigated, retrieved from initial consultation (t1) and re-assessed at follow-up (t2). Method: Logistic regressions were carried out with sex, gastro-intestinal problems, refusal of the first nutrition, syndrome/intellectual disability, Down’s syndrome, autism spectrum disorder, comorbidity of medical diseases (other than gastro-intestinal problems), restrictive caloric food intake and selective food intake, as the predictor variables from t1, and age-appropriate food intake at t2 as the dependent variable. The potential role of sensory processing problems was reviewed at t2. Results: About 73% had improved towards an age-appropriate food intake. Sex (boys), syndrome/intellectual disability, and a lack of varied nutritional intake at t1 were predictors of a worse prognosis. We found a small, but significant correlation between current selective eating patterns and general sensory processing problems. Conclusion: Feeding disordered children, especially boys, with intellectual disabilities or selective eating patterns are at risk for not achieving an age-adequate food intake at a later age, despite behavioral treatment